As rimas do sexo: a poética (pós)pornográfica em porno pop pocket, de Paula Taitelbaum - Oliveira, Juliana Goldfarb de (2015)
This paper aims to verify the pornographic character and, especially post-pornographic in Porno pop pocket, written by Paula Taitelbaum in 2004 and published by L&PM Publisher. The book is formed by eighty-one poems, none of them receives title – giving idea of continuity – and the sexual content is the conductive wire of them all. The title suggests the relationship betwen pornoghaphy (porno) and market (pop pocket), but the composition through the poetic genre and female authorship transgresses what is usually expected from a pornographic text, ie a narrative built with merely excitatory purposes which is writen and producted by men. Even so, postpornography is a political, artistic and sexual movement, that uses the hegemonic pornography to denature their gender relationships and power. Desires considered abject are put in the Center, as anal sex, prostitution for pleasure or use of dildo, themes that also permeates the work of Paula Teitelbaum. In this sense, I divided the work into two parts, first I seek to understand what pornography is and how it has been developed in our society, in the second part I reflected on pornography through a gender perspective, wondering how women tend be represented and what pornographies resists to the hegemonic model, including Porno pop pocket. To perform such analysis, I primarily used theoretical pornography, as Hunt (1999), Maingueneau (2010) and Moraes & Lapeiz (1984) and scholars of the post-pornography, as Preciado (2014) and Ramos (2015).